Game situation information in video-based perceptual decision making: The influence of criticality of decisions - Spittler, M.; Kremer, P.; McNeil, D. G. (Facta Universitatis: Series Physical Education and Sport, 2010)
This study examined the effects of game situation information, manipulated in terms of time and score, on decisions made in a video-based perceptual test in basketball. The participants were undergraduate university students (n=159) who viewed 21 offensive basketball plays, under two test conditions (low decision criticality; high decision criticality). To manipulate the conditions, prior to each clip, the participants were presented with a description of the remaining time and score differential. High decision criticality situations were characterised by a remaining time of 60 seconds or less and score differentials of 2 points or less. Low decision criticality situations were characterised by remaining time of 5 minutes or more and score differentials of 5 points or more. The participants indicated their decision (pass, shoot, dribble) after the visual display had been occluded for each clip. The results indicated that decision profiles differed under the low and high decision criticality conditions. More pass decisions were made under high decision criticality situations and more shoot decisions under low decision criticality situations. These variations differed according to the type of main sport played but not for the basketball competition level. It was concluded that game situation information does influence decision making and should be considered in video-based testing and training.